Technetium-99m-MIBI-SPECT for prostate cancer diagnosis - Kuru, M.; Talat, Z.; Sağer, M. S.; Demirdağ, Ç. (Ukrainian Journal of Nephrology and Dialysis, 2020)
The gold standard method for prostate cancer diagnosis is a transrectal ultrasonography-guided prostate biopsy. The detection rate of prostate cancer using the biopsy is approximately 25-30%. A non-invasive method Technetium-99m methoxy-isobutyl-isonitrile single-photon emission computed tomography (technetium-99m-MIBI-SPECT) could be used in prostate cancer detected. The study aimed to try to show that Tc99m-MIBI-SPECT, which is performed as a non-invasive method before biopsy in patients with prostate biopsy indication, may prevent unnecessary biopsy among these patients. Methods. Fifty-six patients who were admitted to our clinic for any lower urinary tract symptoms or routine control and who had a digital rectal examination or PSA value indication for prostate biopsy were included in this retrospective study. Technetium-99m-MIBI-SPECT our patients before the biopsy was performed, radiopharmaceutical uptake by the intensity and localization of the prostate was detected. Technetium-99m-MIBI-SPECT localization and intensity of involvement by prostate biopsy results were evaluated by nuclear medicine specialists. Results. The patients’ age and PSA level were 62.8 (31-78) years and 11.3 (2.5-100) ng/ml, respectively. Prostate cancer was detected in 27/56 (48.2%) patients. The suspicious diagnosis in technetium-99m-MIBI-SPECT images was observed in 36/56 (64.3%) patients, but prostate cancer was detected in 20 of them only. The sensitivity and specificity of technetium-99m-MIBI-SPECT were 74% and 45%, respectively. The positive and negative predictive values were 55% and 45% respectively. The diagnostic value of technetium-99m-MIBI-SPECT methods was considered as 58%. Conclusıon: The technetium-99m-MIBI-SPECT method in this study had low sensitivity and specificity for prostate cancer diagnosis. Therefore, we came to the conclusion that technetium-99m-MIBI-SPECT cannot be an alternative diagnostic method.